Reliability Issues of Offshore Wind Farm Topology - Liu, Xu; Islam, Syed (University of Puerto Rico, 2008)
The main development trend of wind power generation system is large offshore wind farms with grid connection. Due to extraordinarily high investment, many technical issues yet to be solved and limited experience, the risk of building offshore wind power generation system is always very high. The study presented in this paper takes a view of the effectof offshore wind farm topology on its reliability. The expected loss of generation capacity (ELGC) is the main reliability index in this paper which will be utilized to demonstrate offshore wind farm reliability issues affected by its topology. The work described in this paper is helpful for offshore wind farm planning.